Urban Regeneration as a New Trend in the Development Policy in Poland - Ciesiółka, Przemysław (Quaestiones Geographicae, 2018)
Regeneration of degraded areas takes an important position in the Polish development policy. It is included in the legal framework resulting from the Regeneration Act and the Physical Planning and Spatial Development Act. It constitutes a significant element in the programming of socio-economic and spatial development. This is largely thanks to the EU funds which are the basis for financing the projects and programmes for regeneration. In the country’s development policy a complex approach to regeneration is promoted, manifested by the concentration of activities in the most neglected areas, integrated activities carried out with a broad social participation which will be continuously monitored and evaluated on this basis. The Polish model of regeneration, formulated in such a way, gives hope for the elimination of critical situations in cities and communes.